Dirichlet process Gaussian-mixture model: An application to localizing coalescing binary neutron stars with gravitational-wave observations. Issue 1 (6th June 2018) - Del Pozzo, W; Berry, C P L; Ghosh, A; Haines, T S F; Singer, L P; Vecchio, A
ABSTRACT: We reconstruct posterior distributions for the position (sky area and distance) of a simulated set of binary neutron star gravitational-waves signals observed with Advanced LIGO and Advanced Virgo. We use a Dirichlet process Gaussian-mixture model, a fully Bayesian non-parametric method that can be used to estimate probability density functions with a flexible set of assumptions. The ability to reliably reconstruct the source position is important for multimessenger astronomy, as recently demonstrated with GW170817. We show that for detector networks comparable to the early operation of Advanced LIGO and Advanced Virgo, typical localization volumes are ∼10 4 –10 5 Mpc 3 corresponding to ∼10 2 –10 3 potential host galaxies. The localization volume is a strong function of the network signal-to-noise ratio, scaling roughly ρ _net^-6 . Fractional localizations improve with the addition of further detectors to the network. Our Dirichlet process Gaussian-mixture model can be adopted for localizing events detected during future gravitational-wave observing runs and used to facilitate prompt multimessenger follow-up.